PROMOTING WORK LIFE BALANCE AMONG HIGHER LEARNING INSTITUTION EMPLOYEES: DOES EMOTIONAL INTELLIGENCE MATTER? - Mardhatillah, Amy; Buana, Dana Riksa (PEOPLE: International Journal of Social Sciences, 2018)
Maintaining a healthy balance between work and non-work demand is not an easy job. Fisher (1999) stated that work life balance can be attained when a person experiences more enhancement and less conflict with regard to his work and non-work issues. This study aims to examine work life balance among employees of a Higher Learning Institution (HLI). 200 respondents participated in the present study. Work Life Balance measured by work life balance scale developed by Fisher (1999). While emotional Intelligence is measured by Wong and Law’s Emotional Intelligence Scale (WLEIS) 2002. Result indicated that, there is a significant relationship between emotional intelligence and work life balance with r (0.145) p <005. Further analysis indicated that, there are no variance between work life balance and emotional intelligence across different age, tenure and job type. It is also found that, the sub scale for use of emotion shows highest correlation with work life balance. Finding in the present study indicated that HLI leader and management should focus on enhancing emotional intelligence among the employees to achieve a work life balance. Result in the present study can be used to design intervention on emotional intelligent as well as the framework on maintaining work life balance among HLI employees.